2022
DOI: 10.1101/2022.06.16.496324
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 infection of human brain microvascular endothelial cells leads to inflammatory activation through NF-κB non-canonical pathway and mitochondrial remodeling

Abstract: Neurological effects of COVID-19 and long-COVID-19 as well as neuroinvasion by SARS-CoV-2 still pose several questions and are of both clinical and scientific relevance. We described the cellular and molecular effects of the human brain microvascular endothelial cells (HBMECs) in vitro infection by SARS-CoV-2 to understand the underlying mechanisms of viral transmigration through the Blood-Brain Barrier. Despite the low to non- productive viral replication, SARS-CoV-2-infected cultures displayed increased apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 127 publications
1
4
0
Order By: Relevance
“…Pericytes expressed a 3.4-fold higher number of TMPRSS-2 mRNA copies (Figure 2B) compared to astrocytes. TMPRSS-2 mRNA expression in human brain cells (hBMVECs) mirrors the finding by Torices et al [39]. Thus, our results not only affirm the earlier study findings but provide additional data on the mRNA level expression of TEMPRSS-2 in brain cells.…”
Section: Discussionsupporting
confidence: 91%
“…Pericytes expressed a 3.4-fold higher number of TMPRSS-2 mRNA copies (Figure 2B) compared to astrocytes. TMPRSS-2 mRNA expression in human brain cells (hBMVECs) mirrors the finding by Torices et al [39]. Thus, our results not only affirm the earlier study findings but provide additional data on the mRNA level expression of TEMPRSS-2 in brain cells.…”
Section: Discussionsupporting
confidence: 91%
“…We have recently described that BBB cells display a unique profile of SARS-CoV-2 receptors, with differential expression of molecules such as ACE2, TMPRSS2, ADAM17 and others in human BMECs, astrocytes, pericytes, microglia and neurons [26]. We have also demonstrated that SARS-CoV-2 leads to minimal productive infection on immortalized HMECs [27], although increased apoptosis and inflammation was triggered in infected cultures. Experimental infection of K18-hACE2 mice or hamsters led to effective infection of BMECs, despite no changes in tight junctions were observed [28].…”
Section: Effects Of Sars-cov-2 On Neural Endotheliummentioning
confidence: 88%
“…Mitochondrial morphology is highly dynamic, being different and adjustable in each cell type and maintains a genetic and biochemical homogeneity by allowing for dilution of toxic superoxide species, mutant mtDNA, and repolarization of membranes during homeostasis, stress and inflammation [194][195][196][197]. Accordingly, we have recently shown that infection of HBMEC by SARS-CoV-2 leads to an inflammatory status with cytokine and chemokine production and remodeling of mitochondrial networks, with increased Mfn2 expression [27]. However, additional studies that focus on the role of host cell mitochondrial remodeling upon SARS-CoV-2 infection, including mitochondrial biogenesis and metabolic responses, remain to be elucidated.…”
Section: Aging and Mitochondrial Dysfunction In Bbb Neuroinflammationmentioning
confidence: 99%
“…32,40 Similar results were found in ZIKV but not WNV infections. 32 Recently, MiNA analysis showed that direct exposure of human microvascular endothelial cells to SARS-CoV-2, in which the viral replication cycle is restricted, 41 led to a remodelling of mitochondrial networks by increasing the mitochondrial footprint and mitochondrial networks as determined by summed branch length analyses, 42 suggesting a hyperfused state. Overall, our data are more consistent with those from HCV studies but also suggest that MD may be selectively manipulated depending on the type of virus and likely cell type.…”
Section: Discussionmentioning
confidence: 99%